Empowering Teachers and Students through Machine Learning Training and Education on Personal Data Protection and Intellectual Property Rights in the Era of Artificial Intelligence - MUHAMMAD SYAHPUTRA NOVELAN; ZULHAM SITORUS; AYUMI KARTIKA SARI (Jurnal Pengabdian Masyarakat Variasi, 2026)
The rapid advancement of Artificial Intelligence (AI), particularly Machine Learning (ML), has significantly transformed the educational sector by enabling the use of intelligent applications to support teaching and learning activities. However, the widespread adoption of AI also introduces new challenges related to personal data protection and intellectual property rights. This community service program aimed to improve the knowledge and competencies of teachers and students regarding the fundamentals of Machine Learning while enhancing awareness of ethical and lawful AI utilization. The program was conducted in the school's computer laboratory and involved teachers and students as participants. The implementation employed the Participatory Learning and Action (PLA) approach, including needs assessment, educational seminars, hands-on training, AI application demonstrations, practical exercises, interactive discussions, and evaluation through pre-tests and post-tests. The training materials covered Machine Learning concepts, AI applications in education, personal data protection, and intellectual property rights. The results demonstrated a significant improvement in participants' understanding of Machine Learning applications in education, the importance of protecting personal data, and respecting copyright and academic integrity. Participants also showed high enthusiasm throughout the training, indicating that the program successfully enhanced both digital literacy and legal awareness. This community service initiative is expected to serve as a sustainable educational model for promoting innovative, secure, ethical, and legally compliant AI adoption within educational institutions.